Kajian Etnobotani Tumbuhan Air sebagai Sumber Pangan dalam Mendukung Ketahanan Pangan Lokal di Perairan Rawa - Alif Afri Diyana Dewi; Rini Pamundhi Bekti; Dominika Jamiyati Hale (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2026)
Pangkalan Bun swamp waters have a diversity of aquatic plants that have the potential to be utilized by the community as a food source to support local food security. This study aims to examine the ethnobotany of aquatic plants as a food source to support local food security in Pangkalan Bun swamp waters. The study used a quantitative descriptive approach through interviews and documentation. Fifteen informants were selected using a purposive sampling technique. The informant selection criteria were the community around the swamp waters. The results showed that there were six types of aquatic plants utilized by the community as a food source, namely water spinach (Ipomea aquatica), genjer (Limnocharis flava), kelakai (Stenochlaena palustris), taro (Colocasia esculenta), pandan (Pandanus amaryllifolius) and watercress (Nasturtium officinale). The plant parts utilized include leaves, young stems, shoots, young flowers, and tubers through processing methods such as stir-frying, boiling, making coconut milk vegetables, fresh vegetables, or food additives. The ethnobotanical index analysis showed that water spinach had the highest UV value of 2.9 and an RFC of 1, indicating high levels of utilization and recognition by the community. Watercress had the lowest UV and RFC values, at 0.8. Aquatic plants have significant potential to support local food security because they are readily available and can be utilized as alternative food sources based on local resources.